Syzygium australe (H.L. Wendl.) B. Hyland and Syzygium leuhmannii (F. Muell.) L.A.S. Johnson Fruit and Leaf Extracts Inhibit Proliferation in Caco2 and HeLa Cell Lines - Shalom, Joseph; Cock, Ian Edwin (Pharmacognosy Communications)
Background: Syzygium australe (H.L.Wendl.) B.Hyland and Syzygium leuhmannii (F.Muell.) L.A.S.Johnson fruit and leaves have high antioxidant capacities and high levels of therapeutic phytochemicals. Despite this, the anticancer activity of T. lanceolata extracts has not been adequately explored. Materials and Methods: This study examined the antiproliferative of S. australe and S. leuhmannii fruit and leaf extracts against Caco2 colorectal and HeLa cervical carcinoma cell lines using MTS assays. The toxicity of the extracts was evaluated using Artemia nauplii lethality bioassays. GCMS headspace analysis was used to putatively identify extract components. Methanolic, aqueous and ethyl acetate extracts of S. australe and S. leuhmannii fruit and leaves inhibited the proliferation of Caco2 and HeLa carcinoma cell lines. The aqueous S. australe fruit and S. leuhmanii leaf extracts were particularly potent inhibitors of Caco2 proliferation (IC50 = 27 μg/mL and 43 μg/mL respectively), although all aqueous extracts were potent to good inhibitors (IC50 values substantially <500 μg/mL) of both Caco2 and Hela proliferation. All methanolic extracts also displayed good or noteworthy antiproliferative activity, although generally with IC50 values substantially higher than the corresponding aqueous extracts. In contrast, the ethyl acetate extracts were generally poor inhibitors, or induced cell proliferation. Conclusion: The antiproliferative activity of the aqueous and methanolic S. australe and S. leuhmannii fruit and leaf extracts support their potential as cancer chemotherapies and highlight the need for further study.
Keywords: Myrtaceae; Riberry; Brush cherry; Anticancer activity; Anti-proliferative activity; Antioxidant capacity.